Pemberdayaan Masyarakat Berbasis Teknologi Akuabisnis untuk Penguatan Pangan di Masa dan Pasca Pandemi Covid-19 - Muh. Ikramullah; HERIANSAH HERIANSAH; Nursyahran Nursyahran; Frida Alifia; Rahmat Januar Noor; Arnold Kabangnga (Institut Pertanian Bogor, 2022)
The aims of implementing the PTDM (Technology Products Disseminated to the Community) program is to increase the resilience of people's knowledge and skills in applying aquabusiness technology, especially making probiotics, making artificial feed made from local raw materials, and cultivating a polyculture system. This community service aims to improve the knowledge and skills of the community in applying aquabusiness technology, especially probiotic production, feed production from local raw materials, and the cultivation of polyculture systems. Service activities through the Technology Products Disseminated to the Community (TPDC) program was conducted in Talaka Village, Ma'rang District, Pangkep Regency, South Sulawesi Province with a total of 20 farmers from the Mina Air Brackish Cultivator Group and the Bujung Tangayya Business Group. The empowerment program is implemented using training methods through non-technical counseling, technical assistance, and plot demonstrations. The achievement of program implementation is determined through evaluation through pre-test and post-test questionnaires as well as observation and performance assessments. The results of the empowerment program have a positive impact on improving the knowledge and skills of partners in applying aquabusiness technology. The empowerment program increased the knowledge and skills of partners in making probiotics by 66.7% to 91.7%, making feed increased by 58.3% to 83.3%, and the knowledge and skills of cultivating the polyculture system increased by 41.7. % up to 83.3%. This increased knowledge and skills has the potential to increase income which can strengthen community food security in the period and post-pandemic Covid-19.